2009
DOI: 10.1016/j.scriptamat.2009.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Complementary use of transmission electron microscopy and atom probe tomography for the investigation of steels nanostructured by severe plastic deformation

Abstract: The properties of bulk nanostructured materials are often controlled by atomic scale features like segregation along defects or composition gradients. Here we discuss about the complimentary use of TEM and APT to obtain a full description of nanostructures. The advantages and limitations of both techniques are highlighted on the basis of experimental data collected in severely deformed steels with a special emphasis on carbon spatial distribution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 34 publications
2
28
0
2
Order By: Relevance
“…While the room temperature stability of the highly supersaturated state of these films is surprising, evidence for similar stability of the supersaturated state of a-Fe may be found in the literature. Detailed atom probe tomography studies on cold-drawn pearlitic steel wires where plastic deformation induces the dissolution of cementite [5,43,44] also suggest a surprising degree of stability of the dissolved carbon. In these observations, the regions corresponding to the dissolved cementite retain a very high carbon concentration (it may remain close to 25 at% C) with a sharp carbon gradient between the prior lamella and the ferrite matrix, the composition decreasing from *25 to \1 at% C over a distance of only *5 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the room temperature stability of the highly supersaturated state of these films is surprising, evidence for similar stability of the supersaturated state of a-Fe may be found in the literature. Detailed atom probe tomography studies on cold-drawn pearlitic steel wires where plastic deformation induces the dissolution of cementite [5,43,44] also suggest a surprising degree of stability of the dissolved carbon. In these observations, the regions corresponding to the dissolved cementite retain a very high carbon concentration (it may remain close to 25 at% C) with a sharp carbon gradient between the prior lamella and the ferrite matrix, the composition decreasing from *25 to \1 at% C over a distance of only *5 nm.…”
Section: Discussionmentioning
confidence: 99%
“…In these observations, the regions corresponding to the dissolved cementite retain a very high carbon concentration (it may remain close to 25 at% C) with a sharp carbon gradient between the prior lamella and the ferrite matrix, the composition decreasing from *25 to \1 at% C over a distance of only *5 nm. The stability of such strong carbon gradients [5,44] at room temperature over periods of days or even months without the formation of carbides suggests a surprisingly high stability of what would be expected to be a highly unstable microstructure. Furthermore, it has been reported that the strong carbon concentration gradients present in the as-drawn material persist even after annealing at 200°C for 1 h [45], though fine-scale precipitation of cementite has also been observed in this temperature range [14].…”
Section: Discussionmentioning
confidence: 99%
“…Atom probe specimens were prepared by standard two step electrochemical polishing [41][42][43][44][45][46][47][48][49][50]. Square rods with a 0.3 Â 0.3 mm cross-section and 20 mm long were cut from the aged sample.…”
Section: Atom Probe Tomography (Apt)mentioning
confidence: 99%
“…APT samples were prepared with their tips perpendicular to the wire axis according to the procedure described in Ref. [32] in order to reduce the local magnification effect [17,33] and to probe as many ferrite subgrains as possible.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…During the past 50 years great efforts have been made to understand the microstructural evolution and its effect on strength upon cold drawing [3][4][5][6][7][8][9]. The most frequently reported finding is deformation-induced cementite decomposition [10][11][12][13][14][15][16][17][18][19] and its "unexpected" consequence on strain hardening, i.e. the decomposition of the hard phase-cementite-surprisingly does not adversely affect the material's strength.…”
Section: Introductionmentioning
confidence: 99%